2018
DOI: 10.5194/acp-18-1307-2018
|View full text |Cite
|
Sign up to set email alerts
|

Resolving nanoparticle growth mechanisms from size- and time-dependent growth rate analysis

Abstract: Abstract. Atmospheric new particle formation occurs frequently in the global atmosphere and may play a crucial role in climate by affecting cloud properties. The relevance of newly formed nanoparticles depends largely on the dynamics governing their initial formation and growth to sizes where they become important for cloud microphysics. One key to the proper understanding of nanoparticle effects on climate is therefore hidden in the growth mechanisms. In this study we have developed and successfully tested tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Estimating how the particle GR varies with time and particle size during a single NPF event involves large uncertainties, and is usually not possible without solving the general dynamic equation in combination with measurement data. The general principles of such approach, along with some examples on its application for measurement data, have been discussed in detail by Verheggen and Mozurkewich (2006), Kuang et al (2012), Yu et al (2016) and Pichelstorfer et al (2018), and thus will not be repeated here.…”
Section: Particle Grmentioning
confidence: 99%
“…Estimating how the particle GR varies with time and particle size during a single NPF event involves large uncertainties, and is usually not possible without solving the general dynamic equation in combination with measurement data. The general principles of such approach, along with some examples on its application for measurement data, have been discussed in detail by Verheggen and Mozurkewich (2006), Kuang et al (2012), Yu et al (2016) and Pichelstorfer et al (2018), and thus will not be repeated here.…”
Section: Particle Grmentioning
confidence: 99%
“…Besides routine observations, comprehensive campaigns like PRIDE-PRD2004, CAREBeijing-2006, and CAREBeijing-2008 were also carried out for a better understanding of NPF and aerosol pollution in representative regions and periods in China. Long-term observations of NPF are relatively rare in China, and only a few studies reported NPF observations covering more than a 1-year period Kivekäs et al, 2009;Yao et al, 2010;Shen et al, 2011;Qi et al, 2015;Peng et al, 2017). The relative short-period observations may not represent varying atmospheric conditions, and therefore, the applicability of these observation results may be limited to specific conditions.…”
Section: Overview Of Npf Research In Chinamentioning
confidence: 99%
“…Besides the condensation sink, NPF events seemed not to be very sensitive to the concentration levels of common gas pollutants in China, such as O 3 , SO 2 , and NO 2 (Zhu et al, 2013;. It was observed that SO 2 concentrations were lower during the NPF event days than during non-event days in the NCP (Herrmann et al, 2014) and Taiwan (Young et al, 2013a), as well as during autumn and winter in the YRD (Qi et al, 2015), whereas higher SO 2 concentrations on NPF days were only observed during spring and summer in the YRD (Qi et al, 2015;Yu et al, 2016), during autumn in the PRD (Gong et al, 2010), and at mountain sites (X. R. . Meanwhile, based on the empirical parameter developed to judge whether NPF will occur or not, the exponent of SO 2 in this empirical parameter was quite small, indicating that there is usually enough SO 2 for NPF to occur under heavily polluted conditions (Herrmann et al, 2014).…”
Section: Npf Frequencymentioning
confidence: 99%
“…While these methods do not account for the effects of coagulation on measured changes in particle size, the literature includes approaches that explicitly account for such effects (Lehtinen et al, 2004;Verheggen and Mozurkewich, 2006;Kuang et al, 2012;Pichelstorfer et al, 2018). Other work has applied the above techniques after confirming that coagulation has an insignificant effect for the analyzed data or explicitly accounting for the effects of coagulation on GR m (Stolzenburg et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%